2023
DOI: 10.1111/dmcn.15555
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a touchscreen assessment tool to screen for cognitive delay at 24 months

Abstract: Early identification of cognitive delay is important to increase early intervention for at-risk children. Such identification is largely reliant on parent-report questionnaires, such as the Parent Report of Children's Abilities, Revised 1 or the Ages and Stages Questionnaire. 2 Depending on the screening results, children may have the opportunity to complete full developmental assessments conducted by trained assessors. These include the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
2
4
1
Order By: Relevance
“…We assessed associations between BabyScreen scores at 18‐ and 24‐months and performance on the MSEL, a behavioral measure of global cognitive skills, both concurrently at these time points and longitudinally (at 5‐, 8‐ and 12‐months). Contrary to prior work showing a relationship between general cognitive ability measured by the Bayley Scales and BabyScreen scores (Casey et al., 2023; Twomey et al., 2021), there were no associations between the BabyScreen and the MSEL at any age. These findings are surprising given that prior work has demonstrated both concurrent relationships between MSEL scores and IC at 9‐months (Holmboe et al., 2018) and longitudinal associations between MSEL at 2‐years and EFs at 6‐years (Stephens et al., 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We assessed associations between BabyScreen scores at 18‐ and 24‐months and performance on the MSEL, a behavioral measure of global cognitive skills, both concurrently at these time points and longitudinally (at 5‐, 8‐ and 12‐months). Contrary to prior work showing a relationship between general cognitive ability measured by the Bayley Scales and BabyScreen scores (Casey et al., 2023; Twomey et al., 2021), there were no associations between the BabyScreen and the MSEL at any age. These findings are surprising given that prior work has demonstrated both concurrent relationships between MSEL scores and IC at 9‐months (Holmboe et al., 2018) and longitudinal associations between MSEL at 2‐years and EFs at 6‐years (Stephens et al., 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…(2021) found that, among infants referred for neurodevelopmental assessment, those who had cognitive scores consistent with developmental delay on the Bayley Scales performed significantly worse on the BabyScreen than infants who had typical development. This is supported in Casey et al.’s (2023) work which found a predictive relationship between BabyScreen scores and Bayley Scales performance. It is possible that, while the BabyScreen can distinguish between infants with cognitive delay and those with typical development, it is less sensitive to individual differences among typically developing infants.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Finally, it may also be reflective of the professional mothers who agree to take part in birth cohort studies, which is generally higher than the general population. We have reported similar high rates of tertiary education in a previous cohort study ( 44 ).…”
Section: Discussionsupporting
confidence: 82%
“…There is emerging evidence that touchscreen technology can provide reliable and valid measures of psychometric performance in children of different ages and cultures, including those in low‐ and middle‐income countries 1–5 . Casey et al have demonstrated the validation of touchscreen technology for screening cognitive delay in infants aged 24 months 1 .…”
mentioning
confidence: 99%